A knowledge creation framework for academia toward agroecological transformations of food systems - Munoz-Araya, Mariana; Williams, Sequoia R.; Geoghan, Peter; Ortiz-Gonzalo, Daniel; Marshall, Krista N.; Brewer, Kelsey M.; Alston-Stepnitz, Eli; Rebolloso McCullough, Sarah; Wauters, Vivian M. (Frontiers in Sustainable Food Systems, 2024)
Industrialized agriculture, characterized by high inputs, large-scale monocultures, and confined livestock production, with a narrow focus on profit, is a major transgressor of societal and planetary boundaries. It fuels climate change, biodiversity loss, water and soil degradation, nutritional deficiencies, public health issues, cultural erosion, and socioeconomic inequalities. As early-career researchers in agricultural sciences, we are concerned about these systemic crises and recognize that participating in normative academic practices without reflection may reinforce the prevailing industrialized food system. Motivated by the dissonance between the potential impact of our work and our vision of a better future, in this paper we describe and challenge academic praxis in agricultural sciences to tackle the interconnected crises. We do this by developing a framework of two drivers of academic knowledge production, power and values, and two mechanisms, motives and relationality. We argue that in the current dominant food system, power is consolidated and hierarchical, driven by the values of growthism and reductionism, motivated by efficiency and productivism, and characterized by extractive and anthropocentric relationality. Furthermore, we highlight evidence of the negative outcomes associated with this system, including the challenges we face and may potentially contribute to as participants. We then envision transformed food systems through examples of counter-hegemonic knowledge production systems, grounded in agroecological principles, in which power is distributed and horizontal, the primary values are solidarity and holism, motives enhance sufficiency and sovereignty, and relationality is reciprocal and based on care. By examining the current system and offering examples of alternatives, we aim to help distinguish between research that upholds the statu-quo and research that fosters change. We aim to inspire ourselves and others to reconnect with our agency and contribute towards transformed knowledge systems where food systems, underpinned by the values of agroecology, are more capable of sustaining life on this planet in an equitable and just manner.